Malawi - Lessons Learned From Public Works Programs - Mohan, P.C. (World Bank, Washington, DC, 2012)
In designing Public Work programs (PWPs), it is important to clarify whether the objectives are developmental or to deal with short-term shocks. PWPs make a significant contribution to sustained poverty reduction only when carefully designed to include a graduation strategy (e.g., economic activities training, savings and life skills training) or where continuity of employment is viable (e.g., financed through routine maintenance budgets). Programs lasting twelve months or more can allow for asset acquisition, training and higher risk economic activity. In this way, beneficiaries can begin to graduate out of PWP employment. Valuable assets have been created under PWPs, contributing to economic growth (environmental protection, access routes etc.). In Malawi, full cost recovery will not be possible for some time. It is therefore essential that PWPs budget for maintenance of such assets. PWPs are a valuable vehicle for developing capacity and empowering local government bodies in Malawi. Adequate provision must be made however, for local government administrative and supervision costs. PWPs are a means of skills transfer in participating communities. As a result, follow-on programs find residual knowledge and organizational capacity in place.